2011
DOI: 10.1371/journal.pone.0021791
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prenatal Diagnosis of Fetal Trisomy 18 and Trisomy 13 by Maternal Plasma DNA Sequencing

Abstract: Massively parallel sequencing of DNA molecules in the plasma of pregnant women has been shown to allow accurate and noninvasive prenatal detection of fetal trisomy 21. However, whether the sequencing approach is as accurate for the noninvasive prenatal diagnosis of trisomy 13 and 18 is unclear due to the lack of data from a large sample set. We studied 392 pregnancies, among which 25 involved a trisomy 13 fetus and 37 involved a trisomy 18 fetus, by massively parallel sequencing. By using our previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
268
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(281 citation statements)
references
References 30 publications
9
268
0
4
Order By: Relevance
“…9,10,15, 16 Palomaki et al 16 and Chiu et al 10 reported false-positive rates of 1.4% and 2.1%, respectively, which were improved in a subsequent study. 9 False-positive SNP calls could be derived from erroneous alignments of short reads. 30 Therefore, different bioinformatics parameters, as well as improvements, in statistical analysis have been investigated by these teams in order to eliminate the erroneous calls and decrease the observed false-positive rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,15, 16 Palomaki et al 16 and Chiu et al 10 reported false-positive rates of 1.4% and 2.1%, respectively, which were improved in a subsequent study. 9 False-positive SNP calls could be derived from erroneous alignments of short reads. 30 Therefore, different bioinformatics parameters, as well as improvements, in statistical analysis have been investigated by these teams in order to eliminate the erroneous calls and decrease the observed false-positive rate.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 As the advent of next generation sequencing (NGS), a lot of effort has been concentrated on exploiting this technology for the measurement of aneuploidies in maternal plasma. [9][10][11][12][13][14] Using this technology, non-invasive prenatal diagnostic (NIPD) for trisomy 21, 18 and 13 has recently reached the clinical setting by analysing the relative amount of chromosomes in circulating cell-free DNA from maternal plasma. 15,16 However, approaches permitting reliable detection of single-gene mutations or single-nucleotide polymorphisms (SNPs) using cell-free fetal DNA in maternal plasma are still under development.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important at early gestational ages, because the fetal fractions rise with increasing gestational age, and in women with high BMI, as fetal fractions are inversely proportional to weight [7,24,25]. To distinguish these minor differences with high confidence a large number of reads is required; because MPSS sequences all chromosomes, approximately 6.3 million uniquely-mapped reads from the entire genome are required to ensure sufficient, e.g., chromosome 21 counts for accurate copy number calls [27,[38][39][40]. Additionally, as only approximately 25% of MPSS-generated reads are uniquely mapped, approximately 25 million raw sequencing reads are required per sample to generate sufficient data for accurate analysis [9].…”
Section: Ngs Nipt Approaches Quantitative Massively Parallel Shotgun mentioning
confidence: 99%
“…We refer to this predetermined set of chromosomes as the " reference chromosomes " , and they are used in the denominator for the ratio calculations. This approach mitigates the need to perform additional corrections on the data [e.g., correction for guanine-cytosine (GC) content used by others] (Figure 1 ) [20,21] . The optimal set of reference chromosomes for each chromosome of interest is determined from results of data on a training set that includes only euploid samples (diploid karyotype).…”
Section: Optimized Chromosome Quantificationmentioning
confidence: 99%